2004
DOI: 10.1074/jbc.m311291200
|View full text |Cite
|
Sign up to set email alerts
|

DUB-3, a Cytokine-inducible Deubiquitinating Enzyme That Blocks Proliferation

Abstract: Previous studies have identified the DUB family of cytokine-regulated murine deubiquitinating enzymes, which play a role in the control of cell proliferation and survival. Through data base analyses and cloning, we have identified a human cDNA (DUB-3) that shows significant homology to the known murine DUB family members. Northern blotting has shown expression of this gene in a number of tissues including brain, liver, and muscle, with two transcripts being apparent (1.6 and 1.7 kb). In addition, expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 51 publications
(60 reference statements)
4
106
0
Order By: Relevance
“…Several lines of evidence have implicated these enzymes in the regulation of cell growth and survival. Constitutive expression of murine DUB-1 has been shown to induce G 1 cell cycle arrest, whereas DUB-2 expression can markedly inhibit apoptosis following cytokine withdrawal (15,17,19,20). In addition, we have confirmed that constitutive overexpression of human USP17 blocks growth factor-dependent cell proliferation (20).…”
Section: Introductionsupporting
confidence: 68%
“…Several lines of evidence have implicated these enzymes in the regulation of cell growth and survival. Constitutive expression of murine DUB-1 has been shown to induce G 1 cell cycle arrest, whereas DUB-2 expression can markedly inhibit apoptosis following cytokine withdrawal (15,17,19,20). In addition, we have confirmed that constitutive overexpression of human USP17 blocks growth factor-dependent cell proliferation (20).…”
Section: Introductionsupporting
confidence: 68%
“…Examples of transcriptional regulation are those affecting mouse DUB-1, DUB-2 and DUB-3, which are induced by inflammatory cytokines (Jaster et al, 1999;Burrows et al, 2004;Baek, 2006), and CYLD that is induced by the activation of the nuclear factor-kB (NF-kB) and MAPK Kinase 3/6 (MKK3/6)-p38 pathways (Yoshida et al, 2005). In addition, many DUB functions are tightly controlled by post-translational modifications .…”
Section: Enzymatic Roles and Regulation Of Dubsmentioning
confidence: 99%
“…Dub3 belongs to the USP group. Whereas Dub1 and Dub2 were identified in mice, Dub3 is their human counterpart [31] . This family of growth-regulatory deubiquitinating enzymes are immediate-early genes and are induced rapidly and transiently in response to cytokine stimuli [32] .…”
Section: The Deubiquitination Of Snailmentioning
confidence: 99%
“…IL-6 is also identified as a major cytokine secreted by BLBC cells and is essential for the CSC-like characteristic of BLBC [41] . Interestingly, Dub3 activity and expression, at both the mRNA and protein levels, can be induced by IL-6 through the JAK/STAT3 signaling pathway [31,38,39] . Consistent with this, we also found that IL-6 rapidly induces Dub3 expression, exerting a maximum effect at 2hr [38] .…”
Section: The Deubiquitination Of Snailmentioning
confidence: 99%